Neuroprotective effect and possible mechanism of edaravone in rat models of spinal cord injury: a protocol for a systematic review and meta-analysis - Xiao-bo Wang; Long-yun Zhou; Xu-qing Chen; Ran Li; Bin-bin Yu; Meng-xiao Pan; Lu Fang; Jian Li; Xue-jun Cui; Min Yao; Xiao Lu (Systematic Reviews, 2023)
Abstract Background Spinal cord injury (SCI) is one of the most disabling neurological conditions, afflicting thousands of human beings. Edaravone, a well-known reactive oxygen species scavenger, is expanding its new scope in field of SCI. The objective of this systematic review is to determine the neuroprotective effects and discuss the underlying mechanism of edaravone in management of SCI. Methods The systematic review will include the controlled studies evaluating the neurological roles of edaravone on experiment rat models following SCI. The primary outcome will be the 21-point Basso, Beattie, and Bresnahan locomotor rating scale. The secondary outcomes will include the preservation of white matter areas and malondialdehyde levels. Two researchers will independently search PubMed, Embase, Web of Science, Scopus and Cochrane Library from their inception date. Following study selection, data extraction, and assessment of methodological quality in included studies using the SYRCLE’s RoB tool, data from eligible studies will be pooled and analyzed using random-effects models with RevMan 5.3 software. In case of sufficient data, subgroup analyses with respect to species, age, gender, injury characteristics, or administration details will be carried out to explore the factors modifying efficacy of edaravone. For exploring the appropriate dose of edaravone, a network meta-analysis approach will be conducted based on the Bayesian method. Importantly, the proposed mechanisms and changes of related molecules will be also extracted from included studies for comprehensively investigating the mechanisms underlying the neuroprotective effects of edaravone. Discussion In this study, we aim to quantitatively analyze the role of edaravone in locomotor recovery and tissue damage in SCI rat model. The efficacy of edaravone in distinct scenarios will be investigated by subgroup analyses, and we expect to predict the candidate dose that offers a superior treatment effect using network meta-analyses. Moreover, a comprehensive framework regarding the neuroprotective mechanisms behind edaravone will be constructed via a combination of systematic and traditional review. This study will bring implications for future preclinical studies and clinical applications of SCI. Nonetheless, in light of the anticipated limitations in animal experimental design and methodological quality, the results in this review should be interpreted with caution.